2018
DOI: 10.1051/e3sconf/20184400015
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological assessment of sewage sludge hygienization in the process of composting with the use of Salmonella Enteritidis

Abstract: Abstract. The aim of the study is to assess effectiveness of sewage sludge composting efficiency on the basis of survival of Salmonella Enteritidis bacteria. Carriers containing a strain of S. Enteritidis were added to three layers of a compost pile made of dehydrated sewage sludge from a mechanical-biological wastewater treatment plant and wheat straw. The maximum time of the bacteria survival was established which was found to be the longest in the bottom part of the heap and was 58 days, whereas in the top … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This is confi rmed by studies (Breza-Boruta and Paluszak 2007) in which the highest fungal content (4600 CFU•m -3 ) was found at the control point located 150 meters from the treatment plant, while in the aeration chambers and in the compost storage area the number of these microorganisms did not exceed 2000 CFU•m -3 . Budzińska et al (2011) also showed that the content of fungi was signifi cant at the control station outside the wastewater treatment plant. At this point, the average number of these microorganisms was higher than at the grit sand catcher and aeration chambers, and comparable to the place of storing sewage sludge.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This is confi rmed by studies (Breza-Boruta and Paluszak 2007) in which the highest fungal content (4600 CFU•m -3 ) was found at the control point located 150 meters from the treatment plant, while in the aeration chambers and in the compost storage area the number of these microorganisms did not exceed 2000 CFU•m -3 . Budzińska et al (2011) also showed that the content of fungi was signifi cant at the control station outside the wastewater treatment plant. At this point, the average number of these microorganisms was higher than at the grit sand catcher and aeration chambers, and comparable to the place of storing sewage sludge.…”
Section: Discussionmentioning
confidence: 92%
“…In research conducted by Budzińska et al (2011) the highest amount of mesophilic bacteria was isolated in the spring and summer period at grids point (2020 CFU•m -3 ) and in the autumn and winter period at the SBR reactor (1562 CFU•m -3 ). In own studies, a relatively high concentration of bacteria was also found at the aeration chamber, however, their number was more than three times lower (495 CFU•m -3 ) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation